IDENTIFYING THE CURRENT STATUS OF LAND TRANSPORT INFRASTRUCTURE IN VIETNAM TO SUPPORT CROSS-BORDER FLOWS IN SOUTHEAST ASIA (PHASE 1 CONCLUSIONS) - Jakub DOŃSKI-LESIUK (Transport Problems)
This article presents selected aspects of the existing land infrastructure system in Vietnam that are important for cross-border transport. The aim of this paper is to present the results of the first phase of the study, which includes the analysis of the condition of the logistics infrastructure that supports the processes of international trade in goods. This phase includes the identification and initial assessment of the usefulness of the components of the logistics system in terms of its functionality and economic efficiency. The results define the scope of work necessary for the proper preparation of the logistics system in Vietnam for the needs related to ensuring the desirable efficiency of logistics corridors connecting Vietnam with China and neighboring regional markets of the Association of Southeast Asian Nations.